Effect Of Air-Fuel Ratio on Temperature Distribution and Pollutants For Biogas Mild Combustion - M. M., Noor; Wandel, Andrew P.; Yusaf, Talal (Universiti Malaysia Pahang, 2014)
This paper examines the effect of air-fuel ratio for Moderate or Intense Low oxygen Dilution (MILD) combustion using a bluff-body burner. Exhaust gas recirculation was used to dilute the oxidizer stream prior to the combustion chamber. A low-calorie biogas fuel which consists of 60% methane and 40% carbon dioxide were used in the simulations using a Reynolds-averaged Navier–Stokes model with the realizable k-epsilon turbulence model. The chamber temperature distribution was found to be in small ranges and almost homogeneously distributed, verifying that MILD conditions were attained. The performance was evaluated based on the level of pollutants (Unburned hydrocarbons (UHC) and carbon-mono oxide (CO)) produced and measured in the exhaust gas. Slightly lean conditions produced negligible pollutants with some excess oxygen measured in the exhaust gas. Under rich conditions, UHC and CO were produced, but when synthetic air containing oxygen with a mole fraction of 7% was used as the oxidizer instead of ordinary air, these levels were significantly reduced.